Information Asymmetries, Rule 13e-3, and Premiums in Going-Private Transactions - Jeffry Davis; Kenneth Lehn (Washington University Law Quarterly, 1992)
Among the questions we examine are the following: Are premiums lower in going-private transactions initiated by managers than in going-private transactions initiated by third parties? Did premiums in management-led going-private transactions increase following the adoption of Rule 13e-3? Are premiums in third-party going-private transactions in which management is likely to be an equity participant (i.e., going-private transactions that presently are exempt from Rule 13e-3) lower than premiums in Rule 13e-3 transactions?
Keywords: Leveraged buyouts; Going private (Securities)